Psychometric testing of the Maltese versions of the Exercise Benefits/Barriers Scale and Exercise Motivation Inventory – 2 - Karl Spiteri I; John Xerri de Caro II; Kate Grafton III; David Broom IV (Health Psychology Research)
# Background